Effect of sodium chloride reduction or partial substitution with potassium chloride on the microbiological, biochemical and sensory characteristics of semi-hard and soft cheeses. (November 2019) - Dugat-Bony, Eric; Bonnarme, Pascal; Fraud, Sébastien; Catellote, Jessie; Sarthou, Anne-Sophie; Loux, Valentin; Rué, Olivier; Bel, Nadège; Chuzeville, Sarah; Helinck, Sandra
Abstract: Sodium reduction in the human diet is currently one of the main concerns for public health agencies and, consequently, has become a challenge for the food industries. In this study, the impact of reduced sodium chloride content (20%) or its partial substitution with potassium chloride in soft ("Camembert"-type) and semi-hard ("Reblochon"-type) cheeses was evaluated. Analyses included physicochemical and biochemical composition, microbial counts, 16S rRNA gene metabarcoding and metatranscriptomic analysis, volatile aroma compounds and sensory analysis. Regarding soft cheeses, the salt content of cheeses affected proteolysis at 21 days of ripening. RNA sequencing revealed that the relative activity of G. candidum increased, whereas that of P. camemberti decreased in reduced salt cheeses in comparison to the controls. Higher global intensity of odor and taste was observed in cheeses with reduced salt content, consistent with higher levels of alcohol and ester components. Regarding semi-hard cheeses, modifications of salt content did not significantly affect either their biochemical parameters and sensory characteristics or their technological microbial composition at day 21 of ripening. Finally, no impact of salt content was observed on the growth of the spoiler Yarrowia lipolytica in soft cheeses. In contrast, reducing salt content increased spoiler growth in semi-hard cheeses, as highlighted by a greater development of Pseudomonas that led to an increase in cheese proteolysis and lipolysis. In conclusion, the effect of reducing salt content is highly dependent on the cheese type. This factor should thus be taken into account by the dairy industry when the reduction of salt content is being considered. Moreover, the quality of raw products, in particular, the level of spoiler microorganisms, must be controlled before use during dairy processes. Graphical abstract: Unlabelled Image Highlights: NaCl content in cheeses was reduced by 20% or partially substituted with KCl. Salt content can be modified in semi-hard cheese without changing its quality. Salt modifies the biochemistry, microbiology and sensory perception of soft cheeses. Spoiler microorganisms must be controlled in cheeses with reduced salt content.